Relating Cultural Distance to Self-Other Agreement of Leader–Observer Dyads: The Role of Hierarchical Position - Vriend, Tim; Rook, Caroline; Garretsen, Harry; Stoker, Janka I.; Kets de Vries, Manfred (Frontiers in Psychology, 2021)
Multisource feedback is important for leadership development and effectiveness. An important asset of such feedback is that it provides information about the self-other agreement between leaders and observers. Self-other agreement relates to several positive individual, dyadic, and organizational outcomes. Given the increasingly intercultural context in organizations, it is imperative to understand whether and how cultural distance between leaders and observers relates to self-other agreement. We hypothesize that cultural distance within leader-observer dyads is negatively associated with self-other agreement. Moreover, we expect that this relationship is stronger for leader-superior than leader-subordinate dyads. We use a unique multi-cultural dataset of 7,778 leaders (52 nationalities) rated by 22,997 subordinates (56 nationalities) and 10,132 superiors (54 nationalities) to test our hypotheses. Results confirm that cultural distance is negatively associated with self-other agreement; we show that this relationship is driven by increased self-ratings and by reduced other-ratings. In addition, we find that these results are more pronounced for leader-superior than for leader-subordinate dyads. Implications for the theory and practice of self-other agreement and multisource feedback are discussed.